Formação do nutricionista na área de nutrição em alimentação coletiva no Brasil - Rocha, Tatiana Evangelista da Silva (Universidade Estadual de Goiás, 2019)
Nutrition in Food Service is one of the areas of activity of the nutritionist who is responsible for planning, organizing, directing, supervising and evaluating food and nutrition services. The objective of this study was to analyze the academic training in the area of Nutrition in Collective Food, in Nutrition courses in Brazil. A documentary research was carried out, starting from the menus available in the institutions' electronic websites. The information searches were carried out in the database of the higher education regulation system, e-mec system of the Ministry of Education, from August to December 2017. 552 institutions of higher education were registered with active registration of courses of Nutrition in Brazil. The information collected was related to the number of authorized vacancies, administrative category, evaluation of the National Student Performance Exam, total course workload and the selected disciplines to represent the Nutrition area in Food Service: Food and Nutrition Units Administration, Supervised Internship in Collective Food and Hygiene and Food Sanitary Surveillance. The highest frequency of Nutrition courses takes place in private higher education institutions, represented by 86.6% (478) of the courses. The average total course workload in Brazil was 3,553h ± 340h, with the majority offered between 3,201h and 3,599h (40,19%), meeting the minimum required by Resolution nº 4/2009 of the National Education Council. The majority of the courses were evaluated with grade 3 in the National Student Performance Exam, and the grades 4 and 5 are mainly in public institutions. The analysis of the menus enabled us to describe that the training of the nutritionist in the area of Nutrition in Collective Food in Brazil has a main focus in the Management and Planning of Food and Nutrition Units and, in relation to the contents of Hygiene and Sanitary Surveillance, one perceives the Emphasis on Good Manufacturing Practices in Food Services and Foodborne Diseases. Contents such as Health Promotion in Food and Nutrition Units, Health Surveillance, Sustainability and Entrepreneurship activities are poorly explored during training, which may limit their action as a health promoter in these scenarios. It was verified the presence of badly prepared menus that do not include all the contents necessary for the professional's training.